The beaten territory [large type] - Samuelson-Brown, Randi (Wheeler large print western series., 2018)
THE BEATEN TERRITORY finds Annie Ryan running a second-rate brothel in 1890s Denver with an eye toward expansion. By chance she encounters Lydia Chambers a society woman suffering from a laudanum habit and a bad marriage, who owns a prized property on the infamous Market Street. Annie's fortunes at the brothel turn on her niece Pearl, a pretty young girl swept up in Denver's underworld of jealousy, booze, and vice--until murder stalks the good-time girls and puts everyone's future in doubt. A rollicking tale of blurred lines, flowing booze, played-out miners and upstairs girls, THE BEATEN TERRITORY delivers a compelling look at the intrigues of the Wild West, where women were enterprising and justice could be had...for a price.